COVID-19 paediatric cavity telecare system: a novel chain key generation and encryption scheme - Joydeep Dey (International Journal of Reconfigurable and Embedded Systems (IJRES), 2022)
In this unprecedented coronavirus crisis, telehealth had emerged as a substitute way of treatment. More specifically, paediatric children are at high risk of outside exposure now. Non critical children must be treated remotely through the tableware system. A key based secured online transmission of an intraoral image of the paediatric cavity has been proposed in this manuscript. A cavity is a dental disease occurring in children. It is mainly caused due to prolonged bacterial infections. Secured online transmission with respect to medical transactions is immensely required in telecare information systems (TIS). Data confidentiality factor is preserved with preference in this proposed technique. A parity based novel chain key (NCK) has been generated and diffused inside the intraoral paediatric cavity image. NCK generation scheme is so highly robust that it gives different combinations after each bit altering. Initial seeds are kept at the dentist and patients, to resist myriad attacks inside the wireless channel, especially during this COVID-19 period. Histogram, floating frequency, and autocorrelation were obtained with accuracy using the proposed technique. Effects were observed by flipping simultaneous bits of the initial key and results were highly acceptable. The time for the proposed key generation has been found to be 514.61 ms. The total cryptographic time has been noted as 3.5983 ms in this technique.